2011
DOI: 10.1111/j.1741-2358.2011.00509.x
|View full text |Cite
|
Sign up to set email alerts
|

New method for determining surface roughness of tongue

Abstract: Objective: The degree of atrophy of the lingual papillae in elderly individuals was evaluated using a quantitative method. Subjects and methods: One hundred and eighty-two subjects living in nursing homes and 20 healthy adults as controls were studied. To express the degree of atrophy of the lingual papillae quantitatively, lingual surface roughness was determined by taking an impression with silicone dental material. Based on the impressions obtained from the elderly subjects, they were classified by three ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…Physical methods, mainly bulk rheology, are used to mimic in-mouth processes while consuming and to predict creamy perception (Janhøj, Petersen, Frøst, & Ipsen, 2006;Jellema, Janssen, Terpstra, de Wijk, & Smilde, 2005;Skriver, Holstborg, & Qvist, 1999). As recently shown, a good correlation was found between the sensory attribute creaminess of yoghurt systems and physical parameters derived from viscometry and frequency sweep curves, and Posthumus funnel (Torres, Janhøj, Mikkelsen, & Ipsen, 2011). Studying solely rheological behaviour often fails to give an adequate description of sensory sensation, particularly of creamy ones, due to the complexity of oral processing.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…Physical methods, mainly bulk rheology, are used to mimic in-mouth processes while consuming and to predict creamy perception (Janhøj, Petersen, Frøst, & Ipsen, 2006;Jellema, Janssen, Terpstra, de Wijk, & Smilde, 2005;Skriver, Holstborg, & Qvist, 1999). As recently shown, a good correlation was found between the sensory attribute creaminess of yoghurt systems and physical parameters derived from viscometry and frequency sweep curves, and Posthumus funnel (Torres, Janhøj, Mikkelsen, & Ipsen, 2011). Studying solely rheological behaviour often fails to give an adequate description of sensory sensation, particularly of creamy ones, due to the complexity of oral processing.…”
Section: Introductionmentioning
confidence: 96%
“…To perform tribological measurements, different approaches have been carried out. Some researchers followed the idea to match the properties of a human tongueepalate tribosystem by applying oral tissue such as pigs' tongue (Dresselhuis et al, 2008), by using a rubber band (De Wijk & Prinz, 2005;Tieu & Kosasih, 2007), or silicone samples with well-defined surface structures (Ranc, Servais, Chauvy, Debaud, & Mischler; to simulate tongue roughness properties. Other authors used a rheometer for performing tribological tests of food samples (Goh et al, 2010;Heyer & Läuger, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…As a consequence, the apparent reflection coefficients for R 1 β 1 and R 1 β 2 were helpful in evaluating the impact of β. Prior research has revealed that the R a mean observed for real tongues ranges between 40 and 100 µm, which shows that R 1 β 1 and R 1 β 2 displayed physiological relevant values [48].…”
Section: Impact Of Surface Roughness On R*mentioning
confidence: 94%
“…Surface roughness profile in terms average peak height (R a ) and correlation length (peak width, β) was 103 ± 3 μm and 429 ± 63 μm respectively. For the human tongue, average peak height appears to be 42.5–101.4 μm ( Uemori et al, 2012 ), while peak width appears to be 355–878 μm ( Andablo-Reyes et al, 2020 ).…”
Section: Methodsmentioning
confidence: 99%